Cancer Awareness and Screening Practices of Ghanaian Adults: A Cross‐Sectional Survey - Patrick Kafui Akakpo; Martin Gameli Akakpo (Cancer Reports, 2025)
ABSTRACT Background Cancer screening has been identified as an important contributor to cancer prevention and the control of both morbidity and mortality from cancer. Despite its importance, screening rates have remained low in Ghana. This study investigated some key predictors of screening habits and the rates of awareness for selected cancers that are amenable to screening and early detection. The health belief model provided theoretical support for the investigation. Methods Data was collected from 503 adults in an online survey with a questionnaire, between June and August 2021. Univariate statistical analysis was used to determine the frequencies and percentages of variables. The multivariate analysis used a correlation and a logistic regression to measure association and test a model. Results Participants were aged between 18 and 74 with a mean age of 32.74. Females made up 61.4% of the sample while males accounted for 38.6%. Only 37.6% of participants had previously screened for cancer while 62.4% had never screened. The study hypothesized that age, gender, and Cancer Awareness predict the Cancer Screening habits of respondents. The logistic regression showed that, Age (B = 0.10, SE = 0.01, p = 0.00) and Gender (B = −0.2.71, SE = 0.30, p = 0.00) predicted cancer screening habit. Conclusion Age and gender can predict screening habits. Awareness did not predict screening in this study. The reason and meaning of the findings are discussed and suggestions for improvement of screening uptake and for future research are provided.